FORMULASI DISPERSI PADAT DENGAN PERBANDINGAN KOMPOSISI PARASETAMOL DAN PEG 4000 (1:0,5DAN1:1)MENGGUNAKAN METODE PELEBURAN - Jhon Leonaritua Manullang; Nani Parfati; Karina Citra Rani (Perpustakaan Universitas Surabaya, 2020)
Abstract - Paracetamol is one of drugs which has low solubility property in aqueous medium. This property will affect its bioavailability. Enhancement of solubility can be achieved by formulation of solid dispersion. Paracetamol is dispersed in PEG 4000 as hydrophilic carrier with melting method. To find the effect of the amount of PEG 4000 for the solubility enhancement, two formulas of solid dispersion are made with the ratio of 1:0.5 and 1:1. After the solid dispersion formed, this formula is characterized using FTIR to determine the interactions between paracetamol and PEG 4000 as a sign of formed solid dispersion. After characterization, the amount of paracetamol in the formulationwill be measured. Lastly, dissolution test is performed to find the increase in dissolution rate compared to pure paracetamol powder. Dissolution test profile observation shows that paracetamol and PEG 4000 solid dispersion formulas have lower dissolution rate compared to pure paracetamol. Beside that, the drug content test shows that the content of paracetamol in the dosage form doesn’t meet the quality requirement as established in the Indonesian Pharmacopeia.